Long non‐coding RNA CASC19 facilitates non‐small cell lung cancer cell proliferation and metastasis by targeting the miR‐301b‐3p/LDLR axis. (27th September 2020) - Wang, Lijun; Lin, Cunzhi; Sun, Nina; Wang, Qiang; Ding, Xiaoqian; Sun, Yong
Abstract: Background: Non‐small cell lung cancer (NSCLC) is a lethal tumor resulting in a large number of cancer‐related deaths globally. Long noncoding RNAs (lncRNAs) may modulate tumor initiation and metastasis. Although dysregulation of lncRNA cancer susceptibility 19 (CASC19) is validated in NSCLC, further exploration of the CASC19‐regulated mechanism in NSCLC is still needed. Methods: CASC19 expression was examined in NSCLC cells by a quantitative reverse transcriptase‐polymerase chain reaction. The specific role of CASC19 in NSCLC was analyzed by cell counting kit‐8, EdU, Transwell and western blot assays. The interaction between miR‐301b‐3p and CASC19 or low‐density lipoprotein receptor (LDLR) was confirmed by luciferase reporter and RNA immunoprecipitation assays. Results: CASC19 is markedly overexpressed in NSCLC. Its deficiency impairs cell proliferation, as well as metastasis in NSCLC. Molecular mechanism experiments indicated that CASC19 negatively modulates the expression of miR‐301b‐3p and miR‐301b‐3p can bind with CASC19 in NSCLC. In addition, miR‐301b‐3p binds to LDLR to impair its expression in NSCLC. Finally, rescue experiments showed that miR‐301b‐3p inhibition or LDLR overexpression counteracted the CASC19 knockdown‐mediated function on cell proliferation and metastasis in NSCLC. Conclusions: CASC19 facilitates NSCLC cell proliferation and metastasis by targeting the miR‐301b‐3p/LDLR axis, offering a possible strategy for lncRNA‐targeted treatment in NSCLC. Abstract : Long non‐coding RNA CASC19 facilitates non‐small cell lung cancer cell proliferation and migration. CASC19 acts as a competing endogenous RNA by sponging miR‐301b‐3p to up‐regulate low density lipoprotein receptor.